Students’ Perception on Teacher-Students’ Interaction in an Online Learning Environment - Franssisca, Ruth Eliana; Lestariningsih, Fransisca Endang (JOLLT Journal of Languages and Language Teaching, 2021)
Online learning environment is one of the ways to conduct a learning activity. It usually uses some internet-based programs to support the learning activity including teacher-students’ interaction. Many challenges are considered to occur more on online learning rather than on site learning. Due to its limitation, online learning environment is questioned to be an effective way in providing interaction among teacher and students. Thus, this paper aims to find students’ perspective of teacher-students interaction in an online learning environment. Moreover, to collect the data from the participants, this study used an interview to get in-depth information to see students’ perspective on the related topic. The result shows that two-ways discussion was preferably chosen by the participants and feedback should be given orally, rather than in written form, to help the participants understand more about the materials.